Die Samaritaner und die Bibel / The Samaritans and the Bible: Historische und literarische Wechselwirkungen zwischen biblischen und samaritanischen Traditionen / Historical and Literary Interactions between Biblical and Samaritan Traditions = The Samaritans and the bible : historical and literary interactions between biblical and samaritan traditions - Frey, Jörg; Schmid, Konrad (Studia Samaritana, 2012)
The history and writings of the Samaritans remain an often overlooked subject in the field of biblical studies. This volume, which assembles papers presented at a 2010 symposium held in Zurich, illuminates the history of the Samaritans as well as passages that address them in biblical sources. Through a subsequent comparison to perspectives found in Samaritan sources concerning biblical, early Jewish, and early Christian history, we are presented with counterpoising perceptions that open up new opportunities for discourse. Jörg Frey,Ursula Schattner-Rieser und Konrad Schmid, Universität Zürich, Schweiz.